ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI DAMPAK NEGATIF KEUANGAN - Franky Franky (KELOLA: Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the effect of equity, retained earnings, net operating income, cash flow, interest rates, and exchange rates on financial distress. This type of research is descriptive quantitative which aims to determine the effect of the independent variables on the dependent variable. The sample used in this study is automotive issuers during the 2015-2019 period. Researchers used SPSS and Microsoft excel programs as data processing tools. Based on the t test, retained earnings have an effect on financial distress, cash flow has an effect on financial distress, interest rates have an influence on financial distress, the exchange rate has an influence on financial distress. Based on the F (simultaneous) test, the six variables have a significant effect on financial distress. Based on the results of the analysis also obtained a regression equation [Y=1.58 + 2.68E-14 (X1) + 3.51E 13 (X2) + 4.853 (X3) + 1.62E-5 (X4)].